Literasi Digital dalam Pembelajaran PPKn untuk Meningkatkan Civic Skills Mahasiswa di Era Digital - Alika, Raya; Natasyah, Putri; Ayu, Intan Sekar; Saputra, Riko (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
This research analyzes the implementation of digital literacy in Civics Education (PPKn) learning to enhance students' civic skills in the digital era. Using a qualitative approach with literature study methods, this research examines various scientific journals, books, and relevant articles published in the last 10 years. The results show that digital literacy integration in PPKn learning effectively improves students' understanding of digital ethics, critical thinking abilities, and participation in digital spaces. The main challenges identified include digital infrastructure limitations, digital literacy gaps between educators and students, and lack of relevant digital content. The study concludes that digital literacy plays a crucial role in developing civic skills needed for students to become responsible and active digital citizens. Recommendations include systematic integration of digital literacy in PPKn curriculum, continuous educator training, and collaboration between educational institutions and government.